A deworming field trial with ivermectin (MSD) in reindeer - Nordkvist, M.; Christensson, D.; Rehbinder, C. (Rangifer, 1984)
This paper is to be regarded as a follow-up under field conditions of Nordkvist et al. (1983) as far as ivermectin is concerned. 54 reindeer calves (29 males + 25 females), as far as possible of normal size, were selected November 15th, 1982 from a reindeer herd belonging to Maskaure sameby, Arvidsjaur. The calves were individually branded, by means of ear tags and weighed. 29 calves (15 males + 14 females) were treated with ivermectin (Ivomec 1% MSD) at a dose rate of 1 ml per calf (roughly corresponding to 200 meg ivermectin per kg body weight), subcutaneous injection. Remaining 25 calves (14 males + 11 females) served as untreated controls. The entire group of calves was then returned to the herd for free grazing during winter. During the winter 3 treated calves were found dead, all three of them had been suffering from keratoconjunctivitis. If any of the control animals had succumbed during the same time is not known. On April 21st, 1983 (approx. 150 days post treatment) 44 calves (24 treated + 20 controls) were weighed. 5 treated and 5 controls were randomly selected for slaughter. Carcasses and organs were thoroughly examined from a parasitological and, as far as lungs were concerned, pathological point of view. The efficacy of the treatment was 100(M> or nearly 100% against Oedemagena tarandi, Cephenemyia trompe, Dictyocaulus viviparus, Elaphostrongylus rangiferi, and nematode eggs in faeces. The efficacy against gastrointestinal nematodes was, probably due to date of treatment, somewhat difficult to judge (Tab 1). A statistical analysis of the weight changes, relative to initial weights, (Tab. 2) supports the statements — that all animals had lost weight — that treated males had lost significantly less of their body weights than control males — That weight change of treated females did not differ significantly from that of control females — that the average weight loss of the entire treated group was significantly less than that of the control group. Ett fältavmaskningsförsök med ivermectin (MSD) på renar. Abstract in Swedish / Sammanfattning: 54 renkalvar (29 m + 25 f) såvitt mojligt av normal storlek, utvaldes den 25 november 1982 ur en renhjord tillhorig Maskaure sameby, Arjeplog. Kalvarna mdividmårktes med oronknappar och vågdes. Av dessa behandlades 29 kalvar (15 0*0" + 14 $9) med ivermectin (Ivomec, 1% MSD), 1 ml per kalv, subkutan injektion. Resterande 25 kalvar fungerade som obehandlade kontrolldjur. Den 21 april 1983 (efter 147 dagar) vågdes ånyo 44 (24 behandlade + 20 kontroller) av de ursprungliga djuren. 5 renar i vardera gruppen slaktades och kropp och organ undersoktes parasitologiskt. Effekten av behandlingen var 100% eller nåstintill mot Oedemagena tarandi, Cephenemyia trompe, Dictyocaulus viviparus, Elaphostrongulus rangiferi samt vad gällde forekomsten av nematodågg i tracken. Effekten på mag-tarmnematoder var, med hånsyn till behandlingstidpunkten, svårbedomd. Effekten på trichostrongylida lopmagsmaskar var också svårbedomd och diskuteras i texten. Den relativa forandringen av renarnas kroppsvikt, dvs forandringen i forhållande till ursprungsvikten, har beråknats och statistiskt bearbetats. Det kunde då konstateras — att samtliga renar hade forlorat i vikt — att den genomsnittliga viktforlusten hos de behandlade hankalvarna var signifikant lågre ån hos de obehandlade hankalvarna — att den genomsnittliga viktforlusten hos de behandlade honkalvarna ime skiljde sig statistiskt från viktforlusten hos de obehandlade honkalvarna — att den genomsnittliga viktforlusten i hela den behandlade gruppen var signifikant lagre ån i den obehandlade gruppen. Kenttätutkimus porojen matokuurista Ivermectinillä (MSD). Abstract in Finnish / Yhteenveto: Arjeplogissa Maskauren lappalaiskylåån kuuluvasta porotokasta valittiin 25. marraskuuta 1982 54 porovasaa (29 m + 25 f) mikåli mahdollista normaalikokoa. Vasat yksilomerkittiin korvanastoilla ja punnittiin. Nåistå kåsiteltiin 29 vasaa (15 m + 14 f) ivermectinillå (Ivomec, 1 % MSD), 1 ml vasaa kohden, ruiskutcttuna nahan alle. Loput 25 vasaa toimivat kåsittelemåttominå tarkkailuelåiminå. 21 huhtikuuta 1983 (147 påivån jålkeen) punnittiin uudelleen 44 (24 kåsiteltyå + 20 tarkkailuelåintå) alkuperåisistå elåimistå. Joka ryhmåstå teurastettiin 5 poroa ja ruho ja sisåelimet tutkittiin parasitoloogisesti. Kåsittelyn vaikutus oli 100% tai låhes tåydellinen seuraavia kohtaan: Oedemagena tarandi, Cephenemyia trompe, Dictyocaulus viviparus, Elapohostrongylus rangiferi sekå myoskin mitå tulee matojen munien esiintymiseen sonnassa. Vaikutus maha - ja suolistomatoihin oli, kåsittelyn ajankohdan huomioonottaen, vaikeasti ratkaistavissa. Vaikutus juoksutusmahoihin (trichostrongylida) oli myos vaikeasti ratkaistavissa ja siitå keskustellaan tekstisså. Porojen ruhojen painon suhteellinen muutos, t.s. muutos suhteessa alkuperåispainoon on arvioitu ja tilastollisesti kåsitelty. Voitiin silloin todeta — ettå kaikki porot olivat kevcntyneet painossaan, — ettå kåsiteltyjen urosvasojen keskimååråinen painonvåhennys oli merkitsevåsti alhaisempi kuin kåsittelemåttomien urosvasojen, — ettå kåsiteltyjen naarasvasoien keskimååråinen painonvåhennys ei eronnut tilastollistesti kåsittelemåttomien naarasvasojen painonvåhennyksestå, — ettå koko kåsitellyn ryhmån keskimååråinen painonvåhennys oli merkitsevåsti alhaisempi kuin kåsittelemåttomåsså ryhmåsså.